Mass torts in a world of settlement - Nagareda, Richard A. (Chicago, [Ill.] ; London : University of Chicago Press, 2007)
The traditional definition of torts involves bizarre, idiosyncratic events where a single plaintiff with a physical impairment sues the specific defendant he believes to have wrongfully caused that malady. Yet public attention has focused increasingly on mass personal-injury lawsuits over asbestos, cigarettes, guns, the diet drug fen-phen, breast implants, and, most recently, Vioxx. Richard A. Nagareda's 'Mass Torts in a World of Settlement' is the first attempt to analyze the lawyer's role in this world of high-stakes, multibillion-dollar litigation.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Torts -- United States; Class actions (Civil procedure) -- United States; Complex litigation -- United States; Law; Jurisprudence & general issues; Law of torts, damages & compensation